The Trajectory of Transnational Security in West Africa: Recalibrating the Elements of Regional Integration for Strategic Policy Options in the Sahel Region - Abdulyakeen, Abdulrasheed; Mumuni, Nurain Abayomi (Journal of Contemporary International Relations and Diplomacy, 2024)
The instability and crises in West Africa and the Sahel have changed the security landscape in the region. There has never been a more urgent need for a more cooperative regional environment due to the increasing mobility of conflicts. Methodologically, qualitative and content analysis was employed. Findings revealed that the Sahel region as a whole is characterized by the challenges of establishing governmental authority and promoting development across large and sparsely populated areas in poor institutional environments. The study also revealed that the Sahel’s illegal trade in commodities and people has generally suffered as a result of the violence, and many issues related to human security are transnational in nature. As a result, Mauritania’s president, Mohamed Ould Abdel Aziz, inspired the G5S to forge unity among governments with longstanding rivalries in order to combat the insecurity that has been perceived as a regional issue in 2014, while serving as president of the African Union (AU). The study concludes that, the social, ethnic, and religious heterogeneity of the region, the plurality of threats, and the permeability of territories that necessitate cross-border synergies make it exceedingly difficult to pursue a "comprehensive" approach or "integrated" response to terrorism in the Sahel, for previous approaches to the Sahel were likewise beset by a lack of cooperation in the formulation and application of response plans. There is a need for nations in the region to have the power to address the risks to peace and security, but first, they must all get over a number of internal challenges. Each nation has a stake in enhancing stability.